Equus caballus papillomavirus type 2 (EcPV2) in co-occurring vulvar and gastric lesions of a pony. (October 2020) - Porcellato, Ilaria; Modesto, Paola; Cappelli, Katia; Varello, Katia; Peletto, Simone; Brachelente, Chiara; Martini, Isabella; Mechelli, Luca; Ferrari, Angelo; Ghelardi, Alessandro; Razzuoli, Elisabetta
Abstract: In horses, squamous cell carcinomas (SCCs) are the most common malignant tumors developing on non-pigmented skin, muco-cutaneous areas, like external genitalia, and, less frequently, in the stomach. Growing evidence suggests Equus caballus papillomavirus type 2 (EcPV2) as causative agent of genital SCCs. Our case report describes a 20-year-old, female, mixed-breed pony with co-occurring vulvar papilloma and in situ carcinoma and gastric SCC. Both lesions were positive for the same EcPV2, as confirmed by DNA sequencing. E6 mRNA expression was observed both in vulvar lesions and gastric SCC, while L1 mRNA was expressed in the vulvar tumor. To the best of the Authors' knowledge, this is the first report of an association between EcPV2 and equine gastric squamous cell carcinoma, with co-occurring EcPV2-positive genital lesions. Further studies are required to assess the real prevalence and the possible role of this viral type in these equine tumors. Highlights: Evidence of EcPV-2 transcriptional activity was found in a gastric SCC in a pony. Gastric SCC and vaginal precancerous lesions tested positive for the same EcPV2. EcPV-2 might be involved in the pathogenesis of equine gastric squamous cell carcinomas.